Comparison of the Isometric Hip Flexors Strength in Supine Position in Subjects With and Without Weak Isometric Core Strength - In-Cheol Jeon (Korean Research Society of Physical Therapy, 2021)
Background: Hip flexor muscles are very important in the hip joint structure as a mover and stabilizer. In addition, isometric hip flexor strength in the supine position needs to be considered with isometric core strength (WICS) to measure a precise strength in a clinical way. Objects: We compared isometric hip flexor strength in the supine position in subjects with and without WICS (between factors) and conditions with and without an external support (within factors). Methods: A total of 34 subjects (16 with WICS, 18 without WICS) participated in this study. We used the double-bent leg-lowering test to divide the subjects in two groups according to the presence of WICS. Isometric hip flexor strength was evaluated in the supine position both with and without an external support condition. The two-way mixed analysis of variance was applied to identify significant differences between groups (with vs. without WICS: between factors) and conditions (with vs. without an external support: within factors). Statistical significance was set at α = 0.05. Results: In subjects with WICS, isometric hip flexor strength was greater with an external support than without it (p = 0.0064). In subjects without WICS, there were no significant differences in isometric hip flexor strength in the presence or absence of an external support (p = 0.075). The isometric hip flexor strength was significantly greater with an external support condition in particular in subjects with WICS. Conclusion: The findings of this study reported that an external support condition in individuals with WICS may contribute to the improvement of isometric hip flexion strength in the supine position. Therefore, isometric core strength should be evaluated to distinguish the weakness between core region and hip flexors.